Redesign of the Australian Cystic Fibrosis Data Registry: A multidisciplinary collaboration. (March 2021) - Ahern, Susannah; Dean, Joanne; Liman, John; Ruseckaite, Rasa; Burke, Nettie; Gollan, Morgan; Keatley, Lucy; King, Susannah; Kotsimbos, Tom; Middleton, Peter G.; Schultz, Andre; Wainwright, Claire; et al.
Abstract: Clinical registries that monitor and review outcomes for patients with cystic fibrosis have existed internationally for many decades. However, their purpose continues to evolve and now includes the capability to support clinical effectiveness research, clinical trials and Phase IV studies, and international data comparisons and projects. To achieve this, registries must regularly update the information that they collect and ensure design that is adaptable and flexible to changing needs. The Australian Cystic Fibrosis Data Registry commenced in 1998, and in 2018–19 undertook a transformation to enable it to meet the needs of multiple stakeholders into the future. This included a comprehensive, multidisciplinary review of the registry's data elements, and a redesign and rebuild of the registry's database. The data element review comprised the processes of alignment, comparison, selection, consolidation, revision and definition of finalised data elements. The database redesign included attention to each of the registry functions of data collection, storage and management, and reporting. The revision of a national data collection system is a time-intensive process, and requires significant clinical and other expert engagement. The resulting database, while being continually refined, is now fit for purpose to support Australian clinicians and patients with CF to receive best practice care.